2007
DOI: 10.1097/01.jto.0000263708.08332.76
|View full text |Cite
|
Sign up to set email alerts
|

Does Intensive Follow-up Alter Outcome in Patients with Advanced Lung Cancer?

Abstract: In patients with locally advanced NSCLC, frequent cross-sectional imaging does not alter survival after combined modality therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…Benamore et al compared 40 stage III patients who underwent the INT 0139 and INT 1060 intergroup trials and received intense surveillance against 35 patients with the same stage followed by chest radiograph. Although more recurrences were detected in the trial group, there was no significant difference in overall survival ( p =0.67) [20]. A recent meta-analysis examined the effect of intensive surveillance on survival from several heterogeneous series [21].…”
Section: Commentmentioning
confidence: 99%
“…Benamore et al compared 40 stage III patients who underwent the INT 0139 and INT 1060 intergroup trials and received intense surveillance against 35 patients with the same stage followed by chest radiograph. Although more recurrences were detected in the trial group, there was no significant difference in overall survival ( p =0.67) [20]. A recent meta-analysis examined the effect of intensive surveillance on survival from several heterogeneous series [21].…”
Section: Commentmentioning
confidence: 99%
“…Nakamura et al 17 reported similar survival for stage I patients utilizing surveillance with CT and CXR vs. CXR alone. Benamore et al 15 found that, for stage IIB–III patients, follow-up with routine CT offered earlier detection of successive malignancy but did not result in improved survival, versus CXR. Virgo et al, 18 comparing ‘non-intensive’ vs. ‘intensive’ follow-up that included more frequent CT imaging, found that intensive follow-up did not improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…14,16-18 Many patients with surveillance detected recurrent cancer will be eligible for secondary therapy with curative intent. 10,12,16,17,19-22 Data regarding the impact of surveillance on improved survival have been mixed however. At least one study has demonstrated improved 3-year survival following treatment of surveillance-detected recurrence of 31% compared to 13% for those detected by symptoms.…”
Section: Commentmentioning
confidence: 99%
“…10,12,21,24-27 Still others report no difference in overall survival for surveillance programs. 1728 …”
Section: Commentmentioning
confidence: 99%